Athorough Quality Management Standards for the Library Group of the Faculty of Science Library at the University of Zakho: An Analytical Study - Khaled, Fadia A. (Humanities Journal of University of Zakho, 2015)
The Research aims to identify the total Quality management in libraries and information centers according applied standards in book selection process available in library faculty of science in university of Zakho . The case study is depended on actual survey for books in chemistry science by used group of standards on selection process. The survey method is used for users opinions and interview with staff in the library and selection files and questionnaires tools for collecting data .The Research results are :The book checking and selection committee is the first standard applied .The collection evaluate remove committee is the first standard recent 95%.The important recommendations are :Its necessary to applied TQM used in this research in :Book selection process before buying it to insure users needs.Select the books contains illustration .Select books cover curriculum and specific field .